A novel high-efficiency searchable encryption scheme under robot cloud computing environment. (3rd January 2023) - Wang, Zhongli; Ju, Aiyun
This paper proposed a high-efficiency searchable encryption scheme under cloud computing environment. Through the matching calculation of keyword index set and keyword trapdoor generated by the data user, the searchable encrypted mechanism is realised. By utilising the powerful computing resources of the cloud server, the pre-decryption operation is introduced to reduce the computing time cost of the data user. The cloud server does not know anything about the original file in the cloud through a trapdoor corresponding to the user-provided keyword (the trapdoor retrieves files containing a specific keyword from a large number of encrypted files). Security analysis shows that the new scheme cannot leak data privacy information and has stronger security than other state-of-the-art schemes.